Smectite for acute infectious diarrhoea in children (Review) (2018)
ABSTRACT: BackgroundAs mortality secondary to acute infectious diarrhoea has decreased worldwide, the focus shiFs to adjuvant therapies to lessen the burdenof disease. Smectite, a medicinal clay, could oNer a complementary intervention to reduce the duration of diarrhoea.ObjectivesTo assess the eNects of smectite for treating acute infectious diarrhoea in children.Search methodsWe searched the Cochrane Infectious Diseases Group Specialized Register, the Cochrane Central Register of Controlled Trials (CENTRAL),MEDLINE (Pubmed), Embase (Ovid), LILACS, reference lists from studies and previous reviews, and conference abstracts, up to 27 June2017.Selection criteriaRandomized and quasi-randomized trials comparing smectite to a control group in children aged one month to 18 years old with acuteinfectious diarrhoea.Data collection and analysisTwo review authors independently screened abstracts and the fulltexts forinclusion, extracted data, and assessed risk of bias.Our primaryoutcomes were duration of diarrhoea and clinical resolution at day 3. We summarized continuous outcomes using mean diNerences (MD)and dichotomous outcomes using risk ratios (RR), with 95% confidence intervals (CI). Where appropriate, we pooled data in meta-analysesand assessed heterogeneity. We explored publication bias using a funnel plot.Main resultsEighteen trials with 2616 children met our inclusion criteria. Studies were conducted in both ambulatory and in-hospital settings, andin both high-income and low- or middle-income countries. Most studies included children with rotavirus infections, and half includedbreastfed children.